Pengawasan Pengelolaan Limbah Industri Batu Alam oleh Badan Lingkungan Hidup Daerah Kabupaten Cirebon (Studi Kasus di Kecamatan Dukupuntang) - Neneng Nuraeni; Moh Taufik Hidayat; Sri Wulandari (Jurnal Ilmiah Publika, 2014)
ABSTRACT The title of the study is: “Controlling Management Waste Industry Natural Stone By Environmental Local Government at Cirebon District (Study Case at Kecamatan Dukupuntang)”. Execution management waste industry natural stone of industry at Cirebon District which not appropriate with regulation Undang-Undang which behavior disturb can cause damage surround, until a necessary and society. Research this reciece koranic verse and answer set of problems about execution controlling Environmental Local Government at Cirebon District abaout management waste, deep matter this waste yield industry natural stone. Factor’s which hamper execution controlling Environmental Local Government at Cirebon District about management waste yield industry natural stone. This research included type research kualitative with interview, direct observation, and study literature. Direct study with interview with official Environmental Local Government at Cirebon District is institiution which have authority deep matter which ink to each other with surround, included only wrong is controlling. Form controlling which behavior is permission procedure for agent business with equip brief team, commit controlling to business with intensity two till three rivers deep years’s. Deep framework handle problem’s, as from intern is limitedness SDM which professional and limitedness means operational field for commit controlling. Factor ekstern is less consiouns ness agent effore to obey. Regulation Undang-Undang which behavior, an expensive cos operational to handle waste and less participation society with handle problem live surround.